Tricolor and crescent France and the Islamic world - Watson, William E. (Perspectives on the twentieth century, 2003)
France's contacts with Islam and Moslem populations (especially its fallen Empire and domestic population of Algerians, Turks, and other Muslim immigrants) have conditioned French foreign and domestic policies. After briefly discussing the Crusades, Napoleon's campaigns in Egypt, the French Foreign Legion's campaigns in Algeria and Morocco, and other pre-World War I events, Watson (history, Immaculata College) reviews "contacts" during the 20th century, notably the rise and fall of the French Islamic Empire and the Algerian Crisis